Local and regional management approaches for the redesign of local development: A case study of Greece - Stavros Kalogiannidis; Efstratios Loizou; Dimitrios Kalfas; Fotios Chatzitheodoridis (Administrative Sciences, 2022)
The efforts of different local and regional administrations are increasingly seen as very important drivers of the economic vitality and well-being of territories in a world where subnational government levels continue to gain levels of authority. This study sought to investigate the efficacy of revamping local and regional development through local and regional management practices with a key focus on Greece. A mixed-methods research design was utilized; data were collected using a questionnaire from 200 entrepreneurs and investors from the local community in Kozani and through interviews with six local government leaders in Kozani city, Greece. The study shows that effective local-regional management practices normally function within the constraints provided by local contextual circumstances and traits as well as the possibilities offered by them. In this case, localized techniques may be used in areas with varying degrees of ex ante favorability, economic structures, and different resource endowments, as well as capacities that are essential for regional and local development. Any barriers that may affect the effectiveness of local-regional management practices can be eliminated through proper decision making, the proper allocation of resources, and participatory leadership at the local government level.
Keywords: 350; Greece; local development; local government; redesign; regional development